Harnessing adapted capsule networks for accurate lumpy skin disease diagnosis in cattle - Mallikarjun, Goddeti; Narayana, V. A. (IAES International Journal of Artificial Intelligence (IJ-AI), 2024)
Lumpy skin disease (LSD) poses a substantial risk to livestock, emphasizing the critical need for reliable diagnostic tools to ensure timely intervention. The considerable economic impact of LSD further accentuates the imperative for efficient diagnosis. In this context, artificial intelligence (AI) emerges as a transformative solution, playing a pivotal role in providing swift detection capabilities. Rapid identification of LSD not only alleviates economic burdens but also impedes the disease’s propagation with in herds. A ground breaking in iterative involves the implementation of an adapted capsule network (CapsNet) expressly designed for diagnosing LSD. This innovative strategy is finely tuned to discern intricate patterns in disease manifestation, achieving an impressive accuracy rateof 97.6%. The model’s effectiveness is evident in it is capacity to differentiate between infected and healthy cases, with precision, recall, and F1 score metrics registering at 9.65%, 97.1%, and 96.3%, respectively. This high level of precision underscores the model’s proficiency in minimizing errors, solidifying its role as a dependable tool for precise LSD diagnosis and intervention, contributing significantly to the overall health and economic well-being of livestock populations.